ИНТЕЛЛЕКТУАЛЬНАЯ МОДЕЛЬ УПРАВЛЕНИЯ ТЕМПЕРАТУРОЙ И ВЛАЖНОСТЬЮ ХЛЕБОПЕКАРНОЙ ПЕЧИ: 2 Bread baking and control methods in industrial furnaces (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
Abstract. The paper is devoted to the problem of automated control of the bread baking process in production. An industrial convection oven is considered as an example. The use of artificial intelligence methods for solving this class of problems is justified. An intelligent control scheme based on a fuzzy controller is proposed